Клинико-эпидемиологическая характеристика предменструальных расстройств у девушек-студенток - Белокриницкая, Т.Е.; Фролова, Н.И.; Сутурина, Л.В.; Наджаф-Заде, А.С. (Таврический медико-биологический вестник, 2012)
При анкетному опитуванні студенток медичної академії в 21,3% (115/541) випадків виявлені клінічні симптоми передменструального синдрому (ПМС). Найбільш частими проявами ПМС у студенток 1-3 курсів були мастодинія, здуття живота і збільшення ваги. Цефалгічна, нервово-психічна форми ПМС і передменструальні дисфоричні розлади частіше зустрічалися у студенток 4-6 курсів. The questionnaire survey was done in 541 female medical students and premenstrual syndrome (PMS) was diagnosed in 21,3% of cases (115/541) The most frequent symptoms in female medical students of 1-3 years of study were the following: breast tenderness, abdominal bloating and weight gain. PMS and PMDD (premenstrual dysphoric disorder) were statistically more evident in the 4-6-year female medical students than in students of the 1st -3d years of education.